Wearable robotics: challenges and trends: proceedings of the 5th International Symposium on Wearable Robotics, WeRob2020, and of WearRAcon Europe 2020, October 13–16, 2020 - Moreno, Juan C.; Masood, Jawad; Schneider, Urs; Maufroy, Christophe; Pons, Jose L. (Biosystems & biorobotics, 2022)
Chapter 1: What should we expect from passive exoskeletons -- Chapter 2: Balance recovery support using wearable robotic devices -- Chapter 3: Active Life with Prosthesis -- Chapter 4: Legislation, safety and performance: regulatory aspects in wearable robots -- Chapter 5: The testing of industrial exoskeletons -- Chapter 6: Evidenced-based Indications/Contraindications for and Potential Benefits of Exoskeletal-Assisted Walking in Persons with Spinal Cord Injury.
Keywords: Konferenzschrift; Montage; Berufskleidung; Mechatronik; Rehabilitationsmedizin; Sensortechnik; Mensch-Maschine-System; Ektoskelett; Wearable Computer